THE ENTREPRENEURIAL CAPABILITIES FOR SUSTAINABILITY OF COMMUNITY EMPOWERMENT PROGRAMS - Hukom, Frans Alexander A.; Arbiani, Aulia; Saribanon, Nonon (Universitas Nasional, 2021)
An important aspect of implementing community empowerment programs is that the program is ongoing and sustainable. Entrepreneurial activity is one of the important programs in empowering the community. Therefore, the determining element of the optimal running and continuation of a community empowerment program is the entrepreneurial capabilities of the beneficiaries. Program facilitation generally has limitations in implementing community empowerment, both in terms of budget and program intensity. Therefore, beneficiary business actors need to develop their entrepreneurial capabilities through several training program and facilitator’s assistancy. These capacity building programs and facilitation could develop the sustainability of the implemented activities can be achieved. The entrepreneurial capability development program has been implemented by the Setaria Farmer Group in Kutai Kartanegara Regency, in order to optimize activities and develop product innovations as well as expand market share coverage. Developing exploitative capabilities through various empowerment activities is a provision for the Setaria Farmer Group to utilize honed entrepreneurial capabilities. Afterwards, they can maintain the sustainability of business activities that are being pioneered and developed, including adapting. the market share situation during the Covid-19 pandemic.